A design and optimization method for matching the torque of the wind turbines - Al-Abadi, Ali Kedher Kashin; Ertunc, Özgür; Weber, Horst; Delgado, Antonio (Journal of Renewable and Sustainable Energy, 2015)
An aerodynamic shape optimization method for a horizontal axis wind turbine is developed and verified through experimentation with a laboratory-scale wind turbine. Our method is based on matching the rotor's and the coupled generator's torque. Prior to shape optimization, an initial rotor design is established with a hybrid use of Schmitz and blade element momentum theories. The experimental verification of the developed method is conducted with a small-scale wind turbine; thus, the operating Reynolds number is one order of magnitude lower than large-scale wind turbines. Therefore, a high-lift low-Re airfoil, namely, SG6043, is selected for the blade along the whole span. The shape is optimized by determining the optimum chord and cumulative pitch angle distributions by manipulating the tapering and twisting of the blade. The objective of the optimization is to maximize the turbine's power coefficient Cp, while maintaining the torque equal to that of the generator. The generator's characteristics are found through experimentations which are conducted apart from the wind tunnel experiments. During the optimization process, the local aerodynamic forces on the blade are calculated by interfacing the optimization program with XFOIL; thus, the torque and power can be calculated for the rotor at each iteration step. The optimized turbine performance is evaluated under a design and off-design operating condition. The performance verification experiments are carried out in the wind tunnel with a specially designed setup. A comparison of the measured and computed performance shows good agreement.
UnivIS-Import:2015-07-08:Pub.2015.tech.ITC.stmmec.adesig